A Study of Identity Construction of the Elderly in Weibo News on Public Health Emergency (Sinología hispánica. China Studies Review, 2020)
This paper, taking the perspective of pragmatic identity theory, investigates identityconstruction of the elderly in Weibo news on public health emergency. 157 news reports are collectedfrom three Weibos People’s Daily, WuhanChina as well as Voice of Elderly to explore identity typesconstructed and strategies adopted in constructing the elderly on Weibo. Results show the tendency ofpositive and diversified construction of the elderly in China’s Weibo news on public health emergency.Strategies in constructing the elderly involve identity modifications, identity foregrounding,backgrounding, contrasting and identity shift and crossing.